Comparative safety of chronic versus intermittent benzodiazepine prescribing in older adults: A population-based cohort study. (April 2022) - Davies, Simon JC; Rudoler, David; de Oliveira, Claire; Huang, Anjie; Kurdyak, Paul; Iaboni, Andrea
Background: Benzodiazepine treatment recommendations for older adults differ markedly between guidelines, especially their advice on the acceptability of long-term use. Aims: Using population-based data we compared risks associated with chronic versus intermittent benzodiazepine usage in older adults. The primary outcome was falls resulting in hospital/emergency department visits. Methods: We undertook a retrospective population-based cohort study using linked healthcare databases in adults aged ⩾ 66 years in Ontario, Canada, with a first prescription for benzodiazepines. Chronic and intermittent benzodiazepine users, based on the 180 days from index prescription, were matched (1:2 ratio) by sex, age and propensity score, then followed for up to 360 days. Hazard ratios (HRs) for outcomes were calculated from Cox regression models. Results: A total of 57, 041 chronic and 113, 839 matched intermittent users were included. Hospitalization/emergency department visits for falls occurred during follow up in 4.6% chronic versus 3.2% intermittent users (HR = 1.13, 95% confidence interval (CI): 1.08 to 1.19; p  < 0.0001). There were significant excess risks in chronic users for most secondary outcomes: hip fractures, hospitalizations/emergency department visits, long-term care admission and death, but not wrist fractures. Adjustment for benzodiazepine dosage had minimal impact on HRs. Conclusion: Our study demonstrates evidence of significant excess risks associated with chronic benzodiazepine use compared to intermittent use. The excess risks may inform decision-making by older adults and clinicians about whether short- or long-term benzodiazepine use is a reasonable option for symptom management.